PENGARUH KONSUMSI DAUN SALAM TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI: SYSTEMATIC REVIEW - La Ode Alifariki (NHM PRESS, 2022)
Hypertension is the main cause of cardiovascular disease whose incidence continues to increase in the community that can have a serious impact to cause death or often referred to as the silent killer. One of non-pharmacological therapy is giving boiled of bay leaves. The purpose of this study was to determine the effect of giving bay leaves on blood pressure in patients with hypertension. This study was limited from 2000 to 2022 and found 6 eligible articles sourced from the Google Scholar search engine with the keywords “bay leaves, blood pressure AND hypertension. The results of the study reported that from 6 articles it was found that bay leaves were effective in lowering blood pressure in patients with hypertension.